New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae) - Cao, Yanghui; Dmitriev, Dmitry A.; Dietrich, Christopher H.; Zhang, Yalin (Zootaxa, 2019)
Generic characteristics of three Australian erythroneurine genera are revised based on three new species: Baya lata, Zinga longa and Pettya tenuis spp. nov. Male genitalia characteristics of genus Pettya Kirkaldy are described for the first time.